2008
DOI: 10.1021/jp7120752
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Ionic Liquids with Different Anions Studied by Infrared Vibration Spectroscopy

Abstract: We investigated the structures of ionic liquids (1-butyl-3-methylimidazolium iodide [BMIM][I] and 1-butyl-3-methylimidazolium tetrafluoroborate [BMIM][BF 4 ]) and their aqueous mixtures using attenuated total reflection (ATR) infrared absorption and Raman spectroscopy. The ATR spectrum in the CH x (x ) 1, 2, 3) vibration region from 2800 to 3200 cm [BF 4 ]. These differences are considered to come from the variation in the position of the anion, where I -is expected to be closer to the C(2) hydrogen of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
281
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(309 citation statements)
references
References 40 publications
18
281
0
3
Order By: Relevance
“…71−81 Spectral bands in the region from 3200 to 3000 cm −1 are attributed to the coupled aromatic ring C−H stretching vibrations of the imidazolium hydrogen atoms, while those between 3000 and 2850 cm −1 can be assigned to the aliphatic C−H stretches of the CH 2 and CH 3 groups of the ethyl chain and of the CH 3 group bonded directly to the [C 2 MIM + ] ring. [71][72][73][74][75][76][77][78]81 4 ] thin films to water vapor in the sealed ATR cell at different levels of RH at 295 K. After each RH adjustment, spectra were collected until the band intensities stopped changing to ensure that equilibrium was attained. It typically took ∼20 min for the system to equilibrate.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…71−81 Spectral bands in the region from 3200 to 3000 cm −1 are attributed to the coupled aromatic ring C−H stretching vibrations of the imidazolium hydrogen atoms, while those between 3000 and 2850 cm −1 can be assigned to the aliphatic C−H stretches of the CH 2 and CH 3 groups of the ethyl chain and of the CH 3 group bonded directly to the [C 2 MIM + ] ring. [71][72][73][74][75][76][77][78]81 4 ] thin films to water vapor in the sealed ATR cell at different levels of RH at 295 K. After each RH adjustment, spectra were collected until the band intensities stopped changing to ensure that equilibrium was attained. It typically took ∼20 min for the system to equilibrate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At low RH, there are two well-resolved bands, which can be assigned as the ν 3 asymmetric stretch at 3640 cm −1 and the ν 1 symmetric stretch at 3562 cm −1 of a water molecule that is H-bonded to two [BF 4 − ] anions, as suggested previously. 19,27,30,81,83 As the RH is increased to ∼90% RH, the intensities of the ν 3 and ν 1 O−H stretches increase and the positions shift to ∼3625 and ∼3568 cm −1 , respectively. A "liquid-like" water peak at 3454 cm −1 and a shoulder at 3270 cm −1 also appear and grow, indicative of Equilibrium Molar Fraction of Water in ILs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In comparison to the IR spectra of pure [BMIM][BF 4 ] (Fig. 5b), the presence of 4 ] between 2800 to 3000 cm À1 , originated from the butyl chain attached to the imidazolium ring, and at 3122 and 3163 cm À1 , attributed to the antisymmetric and symmetric C-H vibrational mode of the imidazolium ring, [27] all suggest a [BMIM] [BF 4 ] layer is adsorbed onto the surface of the hybrid materials. As the sample has already been washed repetitively with acetonitrile and ethanol before the spectroscopic measurements, it is concluded that this adsorption is relatively strong.…”
Section: Resultsmentioning
confidence: 93%
“…Further reduction in droplet volume can be achieved by decreasing the size of microstructures and/or using spin coating to achieve thinner IL droplets ( Supplementary Fig. 2d 20 . These liquid-stable IL microdroplets may find applications in understanding the fundamental properties of micro-scale interfaces between immiscible liquids, as well as a range of applications at liquid-liquid interfaces such as electrochemical sensors, solvent extraction, pharmacokinetics and solar energy conversion 21 .…”
Section: Article Nature Communications | Doi: 101038/ncomms4744mentioning
confidence: 99%